Professional integration of university faculty in terms of organisational culture and transition of professional identity - Jatkauskienė, Birutė; Andriekienė, Rūta Marija; Nugaras, Modestas (Social Welfare: Interdisciplinary Approach, 2017)
This article analyses theoretical insights and empirical findings of university faculty’s professional integration. The first part of the research delves into the changes in attitudes and behaviour of university faculty; the second part highlights the factors of teachers’ professional integration in terms of the interiorisation of organisational culture, transition of professional identity. Different approaches to studying the professional integration allows to analyse and then to plan the beginning of a university lecturer’s careers, upon revealing the fact that the career readiness, becoming a professional is not limited only to the knowledge and competencies of any discipline or science. A successful professional integration needs other elements that are important as well. They include the understanding of academic activities, knowledge and performance of various roles by the university faculty, interiorisation of university norms and values, as well as the construction and reconstruction of professional identity.
Keywords: professional integration; interiorisation of organisational culture; professional identity